2021
DOI: 10.1017/s136898002100286x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood anaemia in Brazil: still a serious health problem: a systematic review and meta-analysis

Abstract: Objective: To estimate the prevalence of anaemia in Brazilian children up to 83·9 months old. Design: Systematic review and meta-analysis, using databases PubMed, Scopus, SciELO, Lilacs, Google Scholar, Periódicos Capes, Arca, Biblioteca Virtual em Saúde, Microsoft Academic Search and Cochrane Library using search terms: anaemia, prevalence, child and Brazil. PROSPERO Registration number: CRD42020208818. Setting: Cross-sectional, cohort, case–control and intervention st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 145 publications
0
13
0
3
Order By: Relevance
“…In Brazil, an estimated national prevalence of childhood anaemia was 33 %. However, they were lower in the southern region, where this study was performed (28 %) [53].…”
Section: Discussionmentioning
confidence: 63%
“…In Brazil, an estimated national prevalence of childhood anaemia was 33 %. However, they were lower in the southern region, where this study was performed (28 %) [53].…”
Section: Discussionmentioning
confidence: 63%
“…27 Ferreira, H et al (2020), found a 40 % prevalence in children aged 6 to 60 months 28 and Nogueira-de-Almeida et al (2021) found a 33 % prevalence of anemia in healthy children under 7 years. 29 …”
Section: Data Synthesismentioning
confidence: 99%
“…However, the level of vitamin D fortification is important, as countries with mandatory fortification e.g. Canada and the US, still report high levels of vitamin D inadequacy [27][28][29].…”
Section: Impact Of Increasing Dairy Consumption On Micronutrient Adeq...mentioning
confidence: 99%
“…Iron and zinc are key nutrients for growth and development at this stage. Although iron inadequacy is relatively low in this population, a recent publication reports that 1 in 3 Brazilian children are anaemic [28]. This may be due to the high consumption of rice and beans in the Brazilian diet, as these plant-based sources of iron and zinc are not as bioavailable compared to animal food sources [30].…”
Section: Impact Of Increasing Dairy Consumption On Micronutrient Adeq...mentioning
confidence: 99%